The Impact of Total Quality Management on Human Resource Efficiency in Faisal Islamic Bank of Sudan: A Theoretical and Methodological Framework - Mohanad Mubarak Alajab Fadlalmoula; Eltayeb Ibrahim Ali (White Nile Journal for Studies and Research, 2026)
This study examines the impact of Total Quality Management (TQM) on human resource efficiency at Faisal Islamic Bank of Sudan. It presents a comprehensive theoretical and methodological framework outlining the preparatory stages of the research, including the identification of the research problem, formulation of research questions and hypotheses, and the development of appropriate research instruments. The framework highlights the potential role of TQM in enhancing human resource performance and establishing a foundation for improving employee efficiency and overall service quality. This paper provides an in-depth overview of the research design and preparation process, culminating in the pre-data collection and survey readiness phase, thereby laying a solid groundwork for subsequent empirical analysis and hypothesis testing